Open and distance learning (ODL): seeing from the eyes of English grammar instructors / Nur Hidayah Md Yazid and Melissa Malik - Md Yazid, Nur Hidayah; Malik, Melissa (Universiti Teknologi MARA, 2022)
Grammar teaching is approached differently according to teachers' beliefs and students' needs. It has also long been associated with the usual chalk-and-talk approach. However, due to Covid-19 pandemic, teachers had to leave their comfortable way of teaching and adjust with the unfamiliar virtual approach known as the Open and Distance Learning (ODL). So, how do teachers ensure that students can still learn grammar in ODL? This study investigated lecturers teaching grammar to post-secondary ESL learners at one higher learning institution in the Klang Valley. The study sought to investigate how they responded and adapted to emergent education challenges and strategies used to ensure their students' readiness and learning adjustment. Semi-structured interviews were utilized to gather data. Findings suggested that the lecturers' challenges in adapting to the new norm has led them to reflect on their teaching approach and embrace the use of technology to cope with the teaching and learning process.